THE EFFECT OF THE BUTTERFLY HUG TECHNIQUE ON ANXIETY IN STUDENTS AT STATE MIDDLE SCHOOL 169 WEST JAKARTA - Alifa Ismi; Lailatul Fadilah; Osep Yasier Almunsiri (Poltekkes Kemenkes Banten, 2026)
Background: Anxiety is an undefined and pervasive feeling of discomfort, associated with uncertainty and helplessness. Anxiety can be seen directly through changes in a person's physiology and behavior, both directly and indirectly through cognitive and affective responses. Anxiety in adolescents is often characterized by an emotional state that arises from feelings of stress accompanied by significant physical reactions. Butterfly Hug is a therapy that involves techniques to help individuals feel better by suggesting themselves. This technique can significantly increase blood oxygen levels and provide a sense of calm. Objective: This study aims to determine the effectiveness of Butterfly Hug therapy on anxiety in students of SMP Negeri 169 West Jakarta. Method: This study uses a Quasy Experiment research design with a one group Pre-test and Post-test design. This design does not involve a control group. Result: There is an influence of Butterfly Hug on anxiety with a sig value <0.05, namely a P-value of 0.000. Conclusion: The average level of anxiety before the Butterfly Hug intervention was 30.89 with a min-max anxiety level of 25-41. After the intervention, a value of 14.7 was obtained with a min-max anxiety level of 2-26. So the results show that there is an effect of the Butterfly Hug technique on anxiety.